Effect of growth media components and growth condition on indole – 3 – acetic acid (IAA) production by Pseudomonas putida isolated from soil - Radif , Hala M.; Tawfeeq, Sarah M.; Adnan , Fatimah G.; Hashim, Hadeel D. (Iraqi Journal of Science, 2022)
Pseudomonas putidaPST-1 isolate isolated from soil of plant root was used for high production of indole acetic acid. Indole acetic acid (IAA) production is a major property of rhizosphere bacteria that stimulate and facilitate plant growth. Optimization of indole acetic acid production was carried out at different cultural conditions of pH temperature, incubation period, and the amount of inoculum of bacteria. The best chemical medium for high IAA production (82 Mg/ml) was Luria-Bertani broth medium consisted of 1.2gm tryptophan and 10gm peptone in their components, while the cheese whey medium was the best natural medium for IAA production was (66 Mg/ml). IAA production byPseudomonas putida PST-1 was optimized by studying some factors the results revealed that the maximum IAA value was obtained when the isolate cultivated in Luria-Bertani broth medium supplemented by tryptophan 1.2gm / 1L and peptone 10gm/1L, adjusted at pH 7 and incubated at 30 c for 4 days with the viable count of bacteria was (19,8 × 103). These results suggest that IAA producingPseudomonas putida PST-1 could be promising candidate for utilization in growth improvement of plants of economic and agricultural value.